1995
DOI: 10.1254/jjp.64.155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strontium on Calcium Metabolism in Rats II. Strontium Prevents the Increased Rate of Bone Turnover in Ovariectomized Rats

Abstract: ABSTRACT-Strontium at low doses has been used to treat osteoporosis. However, excessive doses can disturb calcium metabolism. The aim of the present study was to determine a dose that does not have any significant toxic effects on calcium contents in bone and calcium metabolism, and, consequently, to distinguish between pharmacological and toxic doses in rats. The rats were divided into a control, 0.05% Sr, 0.10%-Sr and 0.50%-Sr groups (strontium intake approx. 0, 87.5, 175 and 875 pcmol/day, respectively). Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…An essential function for Li at very low levels of intake has been postulated independently by two groups of investigators using goats [12] or rats [13]. Also promising are the results of Japanese and other investigators [4][5][6][7][8] pertaining the physological role of small quantities of Sr in the context of its positive influence on Ca metabolism in man and animals. Still remains for elucidation the question to what extent Sr and Li may be accepted as essential microelements for animal and man organism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An essential function for Li at very low levels of intake has been postulated independently by two groups of investigators using goats [12] or rats [13]. Also promising are the results of Japanese and other investigators [4][5][6][7][8] pertaining the physological role of small quantities of Sr in the context of its positive influence on Ca metabolism in man and animals. Still remains for elucidation the question to what extent Sr and Li may be accepted as essential microelements for animal and man organism.…”
Section: Resultsmentioning
confidence: 99%
“…In the diet, Sr is strongly discriminated by the organism in favor of Ca [3]. From a more recent paper of Morohashi et al [4] it is evident that stable Sr, in rat experiments (Wistar) at doses below 175 lmol/day, does not have a toxic effect on Ca metabolism and on its content in the bone. At the dose of 87.5 lmol/day these authors observed even some beneficial effects of increased Ca content in the bone.…”
Section: Introductionmentioning
confidence: 99%
“…The currently available data indicate that strontium has metabolic effects on bone in vivo. There is experimental evidence that strontium administration at low dose reduces bone resorption and increases bone formation, resulting in increased bone mass in normal animals [1][2][3][4]. Strontium ranelate (C 12 H 6 N 2 O 8 SSr 2 ), semi-synthetic form of strontium, is the first antiosteoporotic treatment that has dual mode of action and simultaneously increases bone formation, while decreasing bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…400 mg/kg/day, disturbs calcium metabolism in intact rats and produces inhibitory effects on calcium metabolism, such as decreased intestinal calcium absorption, decreased bone formation and resorption, negative calcium balance, and decreased calcium contents in bone (6,7). On the other hand, a strontium-containing substance (S12911) has been shown to prevent femoral osteopenia in OVX rats (8).…”
mentioning
confidence: 99%